GABAergic Gene Regulatory Elements Used in Adeno-Associated Viral Vectors - Duba-Kiss, Robert; Niibori, Yosuke; Hampson, David R. (Frontiers in Neurology, 2021)
Several neurological and psychiatric disorders have been associated with impairments in GABAergic inhibitory neurons in the brain. Thus, in the current era of accelerated development of molecular medicine and biologically-based drugs, there is a need to identify gene regulatory sequences that can be utilized for selectively manipulating the expression of nucleic acids and proteins in GABAergic neurons. This is particularly important for the use of viral vectors in gene therapy. In this Mini Review, we discuss the use of various gene regulatory elements for targeting GABAergic neurons, with an emphasis on adeno-associated viral vectors, the most widely used class of viral vectors for treating brain diseases.